Computer Science in Sport - Special emphasis: Football (Dagstuhl Reports, 2011)
This report documents the program and the outcomes of Dagstuhl Seminar 11271 ``Computer Science in Sport - Special emphasis: Football''. There were five sessions over the course of three days focusing on separate specific aspects on the relevance, applications and current issues pertaining to computer science in sport. The first session on the first day was about RoboCup -- the history, types of games and robots used, and the current topics relevant to machine learning, tracking and planning. The second session on the first day was a miscellaneous session, which looked at broad topics ranging from hardware devices for mobile coaching, uses of positional data in football, rehabilitation methodologies and games for learning. The second day started with a session on modelling sports as dynamical systems combined with the use of neural networks in performance analysis as well as theoretical issues in human movement science. In the afternoon of the second day the session was on topics in computer science specifically relevant to coaches, in which six different people presented. The final day of the conference hosted a session on computer science ``behind the scenes'' of major sports broadcasters and other media. The sessions were attended by academics, graduate students, coaches, performance analysts and athletes.